ETHICS AND BASIC PRINCIPLES OF RESTORING HISTORICAL STONE MONUMENTS - Jadwiga W. Łukaszewicz (Ochrona Dziedzictwa Kulturowego)
The paper discusses ethical guidelines in relation to the conservation of historical monuments made of stone. The presented rules consider the building stone specificity and its susceptibility to various corrosion factors and the character of deteriorated areas in that kind of historic monuments. The basic conservation rule sounding Primum non nocere is deconvoluted to more particular principles like: (i) to preserve authentic historical matter as a carrier of artistic, scientific and historical value of the object, (ii) to provide minimal scale of intervention, (iii) to provide the reversibility of the methods and particularly materials used from conservation or reconstruction works, (iv) to provide distinguishability of reconstructions parts and (v) to provide the integrity of the work of art. The adaptability of these particular rules to the of conservation of stone artistic artefacts is also presented.